1982
DOI: 10.1002/food.19820260138
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of sucrose polyesters in different organ lipids of rats (Short communication)

Abstract: Academy of Sciences of the GDR Accumulaticn of sucrose polyesters in different organ lipids of rats (&or t communication) L. Aust, J. Briickner, R. NoackandG. Mieth Esters of sucrose and long chain fatty acids with 6 and more acyl grwp (polyesters -SPE) are a s undigestible and unabsorbable fat-like compounds of interest a s a fat substitute in dietary food-stuffs for reductirn of energy intake. Furthermore, due to their

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In connection with investigations about the alimentary influence on energy efficiency in rats we have found that a glycine rich diet with sufficient amounts of essential amino acids (mixtures of casein and gelatine) reduces significantly the serum triglyceride level [8]. Changing of dietary amino acid pattern towards an excessive intake of individual amino acids leads among others often to an accumulation of lipids in the liver, as shown mainly in experiments with rats [9-131.…”
Section: Indroductionmentioning
confidence: 94%
“…In connection with investigations about the alimentary influence on energy efficiency in rats we have found that a glycine rich diet with sufficient amounts of essential amino acids (mixtures of casein and gelatine) reduces significantly the serum triglyceride level [8]. Changing of dietary amino acid pattern towards an excessive intake of individual amino acids leads among others often to an accumulation of lipids in the liver, as shown mainly in experiments with rats [9-131.…”
Section: Indroductionmentioning
confidence: 94%
“…61. Earlier animal experiments with 64; '*C-labelled sucrose-octa-palmitate in a semisynthetic diet, however, outlined a very small but not neglectable accumulation raie of lO.-'--lO -5 0 ; in various organs after a feeding time of 7 days or 3 and 6 weeks, respectively [7,8).…”
mentioning
confidence: 96%
“…61. Earlier animal experiments with 64; '*C-labelled sucrose-octa-palmitate in a semisynthetic diet, however, outlined a very small but not neglectable accumulation raie of lO.-'--lO -5 0 ; in various organs after a feeding time of 7 days or 3 and 6 weeks, respectively [7,8).Because nothing is known about metabolic fate of incorporated SPE the study aimed at the elucidation of the metabolic behaviour of SPE after i.v. injection to mimic a higher accumulation rate.…”
mentioning
confidence: 96%